Internalisasi Nilai-Nilai Kolaboratif Siswa Melalui Penerapan Pembelajaran Pada Mata Pelajaran Pendidikan Pancasila Di SMP Negeri 1 Narmada - Refki Putri Muliana Dewi; Muh. Zubair; Bagdawansyah Alqadri (Universitas Muhammadiyah Ponorogo, 2026)
This study analyzes students' internalization of collaborative values through Civics learning at SMP Negeri 1 Narmada. The study aims to describe the implementation of learning that internalizes collaborative values and students' experiences in the process. This study uses a qualitative approach and descriptive research type with data collection through observation, interviews, and documentation. Data analysis includes data reduction, data presentation, and drawing conclusions to ensure validity through triangulation of techniques, sources, and time. Internalization of collaborative values at SMPN 1 NARMADA is carried out through strategies such as small group discussions, make a match, see hear feel and wonder (SHFW), and cross-subject activities.